Clinical characteristics and patterns and predictors of response to therapy in collagenous and lymphocytic colitis. (November 2015) - Colussi, Dora; Salari, Behzad; Stewart, Kathleen O.; Lauwers, Gregory Y.; Richter, James R.; Chan, Andrew T.; Ricciardiello, Luigi; Khalili, Hamed
Abstract Background. Collagenous colitis (CC) and lymphocytic colitis (LC) are chronic inflammatory disorders of the colon. There is a paucity of data on differences in etiology, natural history, and treatment response between CC and LC. Methods. Between 2002 and 2013, we identified new diagnoses of CC and LC using the Research Patient Data Registry in a tertiary referral center. We used chi square or Fischer's exact test and Wilcoxon rank-sum tests to compare the differences in clinical characteristics, treatment types, and response rates between LC and CC. Results: Through 2013, we confirmed 131 patients with a new diagnosis of microscopic colitis (MC) (55 LC, 76 CC). Compared to cases of LC, patients with a diagnosis of CC were more likely to be women (86% vs. 69%, p = 0.03), have elevated erythrocyte sedimentation rate (mean 28 vs. 13 mm/h, p = 0.04), and less likely to be diabetic (5% vs. 18%, p = 0.02). Budesonide was the most effective treatment for both CC and LC (94% and 80%, respectively). However, there were no statistically significant differences in response to various treatments according to the type of MC (all p > 0.10). Older age at the time of diagnosis was associated with better response to bismuth subsalicylate (odds ratio: 1.76; 95% confidence interval: 1.21–2.56 for every 5-year increase) for both CC and LC. Conclusion. Despite differences in the clinical characteristics, response rates to available treatments appeared to be similar in both LC and CC. Older patients may have a better response to bismuth subsalicylate therapy.